Studies of properties of “Pain Networks” as predictors of targets of stimulation for treatment of pain - Lenz, Frederick (Frontiers in Integrative Neuroscience, 2011)
Two decades of functional imaging studies have demonstrated pain-related activations of primary somatic sensory cortex (S1), parasylvian cortical structures (PS) and medial frontal cortical structures (MF), which are often described as modules in a ‘pain network’. The directionality and temporal dynamics of interactions between and within the cortical and thalamic modules is uncertain. We now describe studies of local field potentials (LFP) carried out in an epilepsy monitoring unit over the one week period between the implantation and removal of cortical electrodes during the surgical treatment of epilepsy. These recordings have unprecedented clarity and resolution for the study of LFPs related to the experimental pain induced by cutaneous application of a Thulium YAG laser. We also used attention and distraction as behavioral probes to study the psychophysics and neuroscience of the cortical ‘pain network’. Electrical activation of cortex was measured by event related desynchronization (ERD), over SI, PS and MF modules, and was more widespread and intense while attending to painful stimuli than while being distracted from them. This difference was particularly prominent over PS. In addition, greater perceived intensity of painful stimuli was associated with more widespread and intense ERD. Connectivity of these modules was then examined for dynamic causal interactions within and between modules by using the Granger causality (GRC). Prior to the laser stimuli, attention to the painful stimulus consistently increased the number of GRC pairs both within the SI cortex, and from SI upon PS (SI>PS). After the laser stimulus, attention to a painful stimulus increased the number of GRC pairs from SI>PS, and SI>MF, and within the SI module. LFP at some electrode sites (critical sites) exerted GRC influences upon signals at multiple widespread electrodes, both in other cortical modules and within the module where the critical site was located.